Implementation of Inclusive Education at Elementary Schools During the Covid-19 Pandemic - Irradhiatul Jannah; Hermanto Hermanto (Jurnal Prima Edukasia, 2022)
Education must be open, regardless of race, ethnicity, or characteristics, for a student with a disability. Inclusive education is an alternative that is facilitated by the government to reduce discrimination so that children with special needs can obtain a quality education. However, over time the implementation of inclusive education has been hampered by several obstacles, especially with the current state of the Covid-19 pandemic. Currently, there are still many schools providing inclusive education that do not have special assistant teachers, and there is not even a special budget to provide inclusive education. This study aims to examine and describe the implementation of inclusive education at the Payakumbuh City Elementary Schoolbduring the Covid-19 pandemic. The research is a descriptive-analytic study, and data collection techniques were carried out using observation and interviews. The result of the study found that the implementation of inclusive education at the Payakumbuh City elementary schools had not been running by the criteria for implementing inclusive education. This is due to the absence of a dedicated budget for providing inclusive education, teachers’ misunderstandings regarding the characteristics and needs of students with special needs, limited facilities that accommodate the needs of students with special needs, and pandemic conditions that make the learning process less effective. Therefore, these obstacles in the implementation of inclusive education must be overcome immediately, local governments can consider holding socialization in schools, to provide understanding to teachers, because they are the ones who will teach students with special needs.